Sequencing Batch Reactor-Continuous Flow Effectiveness For Treating Restaurant Wastewater - Mochammad Yusuf Cahayaning Nugraha B; Novirina Hendrasarie (Future Science)
Wastewater produced by untreated restaurants can increase the COD, BOD, TSS, and grease in water content. Household wastewater treatment only uses a grease trap, so it does not meet the quality standards requirement. For this reason, a unit performance evaluation is required. One technology that can improve wastewater quality from grease trap treated wastewater uses a biological process called Sequencing Batch Reactor (SBR). This research is about processing the output of grease trap waste from Padang restaurants using the Sequencing Batch Reactor Continuous Flow unit. C ontinuous influent flow reactor is used in this research. The processed sequentially but discarded intermittently. This study aims to determine the performance of SBR-CF in reducing the content of COD, TSS, Total N, and PO4. SBR-CF was operated with hydraulic retention time (HRT), and the aeration rate varied, which were 12, 24, 36, and 48 hours and aeration rates of 7 L/min and 14 L/min. The results showed that the optimum HRT and aeration rates were 24 hours and 14 L / minute. With the efficiency of removal of COD, TSS, Total N, and PO4 produced respectively 96.9%; 98.63%; 86.72%; and 55,6%